Employee Performance during Covid 19 Pandemic: MARS Model Approach (Journal of Business and Management, 2022)
Abstract. Covid-19 Pandemic caused the disruption of employee behaviour. This research aims to analyze the MARS condition of BRI employee during pandemic and how it affects employee performance. MARS is a model that explains and elaborate an individual behaviour as a result of internal and external factors (McShane and Von Glinow, 2010). It consists of four factors which are motivation, ability, role perceptions, and situational factors. By using the 39 indicators to measure the correlation between MARS model and employee performance, this research gathers 135 sample of BRI employees. The result shows each condition of the variables, motivation (4.152), ability (3.788), role of perception (3.901), situational factors (3.941) and performance (3.985). All of the independent variables affect performance positively while the T-statistic value shows that the motivation (3.933), role of perception (2.459), and situational factors (2.606) affects performance significantly, but the ability (0.404) affects performance insignificantly. As an organization, BRI needs to know what drives employee performance the most during this situation based on MARS model, that is motivation. BRI could start to increasing the variables with following priorities motivation, situational factors, role of perception, and ability.Keywords: Motivation, Ability, Role of Perception, Situational Factors, Performance, Pandemic, Bank, MARS Model